9LTE: Gerakan Literasi Tangkap Edukatif dengan Menekankan The Nine Golden Habits Berbantuan Boneka Tangan bagi Anak-anak di Kampung Pelangi Belawan: Gerakan Literasi - Edy Suprayetno; Fatimah Sari Siregar; Aflahun Fadhly Siregar; Indah Subhini Lubis; Dewi Putri Masri (CERED Indonesia Publishing, 2025)
The community partnership program aims to assist the Fisherman's Children Care Community (IDADA) in implementing out-of-school mentoring and teaching in the concept of religious literacy by emphasizing The Nine Golden Habits, using the 9LTE technique: Educational Capture Literacy Movement with the help of hand puppets to children in Kampung Pelangi Belawan. The Nine Golden Habits with the help of hand puppets aims to help children know and apply Islamic etiquette, the concept of morals towards oneself, morals towards Allah SWT, and morals towards fellow human beings. The team used hand puppet media combined with 9 LTE ??animation, as an intermediary tool for the 9LTE Gymnastic practice (Educational Capture Literacy Movement) emphasizing The Nine Golden Habits, which is a guideline for implementing Islamic practices which contains nine basic habits in order to realize a Muslim personality. the truth. The nine golden habits are the habit of praying, the habit of fasting, the habit of giving zakat, the habit of reading the Koran, the habit of reading books/scriptures, the habit of Islamic civility in every activity carried out, the habit of reciting the Koran and being in a community of pious people, the habit of social organization. and social, habits of positive thinking and smiling, assisted by hand puppets combined with 9 LTE ??animations aimed at making it easier for children to receive material and introduce religious literacy in everyday life.